Systematics and biogeography of the spider genus Mallinella strand, 1906, with descriptions of new species and new genera from Southeast Asia (Araneae, Zodariidae) - Pakawin Dankittipakul (2018)
The systematics status of the spider genus Mallinella Strand, 1906 (Araneae, Zodariidae), the phylogenetic relationship of the species within the genus and its relationships to other zodariids were investigated by means of cladistic analysis of morphological data. Mallinella is redefined and characterized by a single synapomorphy: the presence of posterior ventral spines situated in front of the spinnerets arranged in a single row. The genus is clearly palaeotropical, occurring in Africa, Indian subcontinent, Indo-Burma, Sundaland, Wallacea and Polynesia-Micronesia. Two hundred and two (202) Mallinella species are treated. One hundred and one (101) species are described as new and placed in twenty-two (22) species-groups, making Mallinella the largest zodariid genus. Nineteen (19) species are redescribed, the conspecific sex of seven (7) species is discovered and described for the first time. Fifteen (15) new com binations are proposed. Nine (9) Storena species are here transferred to Mallinella: M. beauforti (Kulczy?ski, 1911) comb. nov., M. sciophana (Simon, 1901) comb. nov., M. sobria (Thorell, 1890) comb. nov., M. fasciata (Kulczy?ski, 1911) comb. nov., M. vicaria (Kulczy?ski, 1911) comb. nov., M. redimita (Simon, 1905) comb. nov., M. melanognatha (van Hasselt, 1882) comb. nov., M. nilgherina (Simon, 1906) comb. nov., M. vittata (Thorell, 1890) comb. nov. Two Storena species are transferred to Asceua: A. dispar (Kulczy?ski, 1911) comb. nov., A. quinquestrigata (Simon, 1905) comb. nov. One Storena species is transferred to Oedignatha (Liocranidae): O. aleipata (Marples, 1955) comb. nov. One Storena species is transferred to Cybaeodamus: C. lentiginosus (Simon, 1905) comb. nov. Storena tricolor Simon, 1908 is transferred to the Asteron complex of Australia. Three Storena and two Mallinella species are misplaced; they belong to undescribed genera (S. kraepelini Simon, 1905; S. lesserti Berland, 1938; S. parvula Berland, 1938; M. khanhoa Logunov, 2010; M. rectangulata Zhang et al., 2011). Mallinella vittata (Thorell, 1890) comb. nov. is revalidated and removed from the synonymy with M. zebra (Thorell, 1881). Storena vittata Caporiacco, 1955 is removed from homonym replacement (S. caporiaccoi Brignoli, 1983) with S. vittata Thorell, 1890 (= M. vittata comb. nov.). Storena annulipes Thorell, 1892 is removed from its preoccupied name with S. annulipes (L. Koch, 1867) in Storena and transferred to Mallinella; its replacement name S. cinctipes Simon, 1893 is suppressed. Zodarion luzonicum Simon, 1893, Storena multiguttata Simon, 1893, S. semiflava Simon, 1893 and S. obnubila Simon, 1901 are regarded as nomina dubia. Six Indian species were misplaced in Storena; they belong to one of the following genera: Mallinella, Heliconilla gen. nov., Workmania gen. nov., Heradion, or Euryeidon. These taxa are S. arakuensis Patel & Reddy, 1989, S. debasrae Biswas & Biswas, 1992, S. dibangensis Biswas & Biswas, 2006, S. gujaratensis Tikader & Patel, 1975, S. indica Tikader & Patel, 1975 and S. tikaderi Patel & Reddy, 1989. They are regarded as species incertae sedis. A new genus, Heliconilla gen. nov., is proposed for nine species, six of which are new to science while the other three are transferred from Mallinella and Storena. These taxa are: H. irrorata (Thorell, 1887) comb. nov., H. oblonga (Zhang & Zhu, 2009) comb. nov., H. thaleri (Dankittipakul & Schwendinger, 2009) comb. nov. Workmania gen. nov. is established to accommodate two species from Southeast Asia; W. juvenca (Workman, 1896) comb. nov. is transferred from Storena. It is unlikely that the origin of Mallinella dates back more than 100 MYA. Mallinella or its ancestor is believed to have evolved during the Cretaceous, after the separation of South America from Gondwana, and the greater part of its evolution took place during the Tertiary. The Asian-Australian lineages of Mallinella could migrate to India via Greater Somalia before or after the K-T extinction (65 MYA), before the Indian subcontinent joined Asia (ca. 45 MYA).The biogeographic history of the genus involves plate tectonics during the Cretaceous and the Cenozoic in combination with climatic changes and alternating climatic cycles which might have led to episodes of range expansion, isolation of populations and allopatric speciation. © 2012 Magnolia Press.